Gender and the south China miracle : two worlds of factory women - Lee, Ching Kwan (University of California Press, 1998)
This study of women workers on either side of the Chinese-Hong Kong border demonstrates how two different factory cultures have emerged from profound economic change. It concludes that the differences in the gender politics of the two labour markets determine the culture of each factory.